Impact of Community Engagement on Sustainable Development Goals (SDGs): The Global Goals to Local Implementation - Mohd Salleh, Kahirol; Sulaiman, Nor Lisa; Puteh, Saifullizam; Jamaludin, Maisarah Auni (Journal of Technical Education and Training, 2023)
The All-Party Parliamentary Group Malaysia - Sustainable Development Goals (APPGM-SDG) is a bipartisan initiative under the Parliament of Malaysia to implement and promote Sustainable Development Goals (SDGs) in Malaysia. The SDGs projects in Malaysia were held through Non-Governmental Organization or the Civil Society Organization alliance with the purpose of raising awareness about the SDGs as well as providing capacity building projects that can give greater impacts on social, economy and wellbeing among Malaysian citizens. The main objective of SDGs projects is to analyse the impacts on SDGs in relations to targets and indicators from solutions providers. The Mixed Methods methodology were used in this project by integrating qualitative and quantitative analysis to discover solution providers expertise in delivering capacity building trainings and beneficiaries outcomes in terms of personal, skills, network, system, SDGs projects and gender constructs. The selected locations within Johor Parliamentary Constituency covered eight SDGs projects associated with community engagement context especially in Technical and Vocational Education and Training (TVET). In addition, the effectiveness of the SDGs projects was measured based on project planning, feasibility and implementation, the main parameters that influence the performance and quality of the SDGs projects by the solution providers. The findings showed the most substantial constructs that influence the greater impact of the SDGs projects to the beneficiaries were personal and technical skills. The lessons to be drawn from the experiences of the selected projects, among others are how effective the SDGs project can helped improve the household income, increased community engagement, and enhanced general well-being in overall.